Internet Supported Psychological Interventions (ISPIs) and Mobile Phone Applications: A Literature Review and Proposed Model - Pieter Rossouw; Francesca Reddington (Psychotherapy and Counselling Journal of Australia)
Internet Supported Psychological Interventions (ISPIs) and mobile phone applications are increasing in the modern mental health care environment, most commonly with anxiety and depressive disorders. These emerging e-mental health services offer increased public access to psychological services that maximise outcomes at reduced cost and therefore are increasingly being endorsed by policy makers, therapists and clients. This paper presents a literature review which shows that ISPIs have consistently demonstrated positive treatment effects and reductions in symptomatology for clients with a range of psychological and physical complaints. However, the issues of support, attrition, usability, and theoretical approach, all warrant further examination. Therefore, the formulation of a new model of mental health care that incorporates ISPIs into everyday practice settings represents an expedition into a new frontier for the brain-wise therapist. A new model of care is proposed in this article that utilises a "bottom-up" neuropsychotherapeutic approach to ISPI development. The model provides standardised homework modules as an adjunct to therapy with feedback to the consulting therapist. This new model of care aims to enhance facilitation and consolidation of neural pathways that promote wellness, down regulation of the limbic response and engagement with higher cortical areas throughout the therapeutic process, whilst providing for the basic needs (attachment, control, self-esteem and pleasure maximisation/distress avoidance) of the client